Development and preliminary testing of an instrument to measure healthiness of lifestyle among breast cancer survivors. Issue 6 (19th May 2014) - Wang, Hsiu‐Ho; Chung, Ue‐Lin; Tsay, Shiow‐Luan; Hsieh, Pi‐Ching; Su, Hui‐Fang; Lin, Kuan‐Chia
Abstract : Monitoring lifestyle to maintain health is an important issue for breast cancer survivors. No multidimensional instrument has previously been available specifically for assessing overall healthiness of lifestyle among breast cancer survivors. This study aims (i) to establish the Healthy Lifestyle Instrument for Breast Cancer Survivors (HLI‐BCS) and (ii) to examine the reliability and validity of the established scale. A quantitative cross‐sectional design was used. This project was conducted in four phases. In phase I, using the Health‐Promoting Lifestyle Profile as the core concept, we created 50 preliminary measurement items. In phase II, we invited 10 breast cancer survivors and five professional experts to conduct a content validity assessment. In phases III and IV, a total of 220 breast cancer survivors were enrolled to assess the construct validity and the internal consistency and reliability. The final HLI‐BCS contains 20 items across five domains: dietary habits, environment and physiology, health responsibility and stress management, social and interpersonal relations and spiritual growth. Through the information presented in the HLI‐BCS, breast cancer survivors can assess their lifestyles on multiple dimensions and subsequently adjust their lifestyles to enhance their recovery and quality of life.